Diagnostic Accuracy of Ultrasonography by Emergency Medicine Resident in Detecting Intestinal Obstruction; a Pilot Study - Sabzghabaei, Anita; Shojaei, Majid; Chavoshzadeh, Miromid (Archives of Academic Emergency Medicine, 2022)
Introduction: There are many ambiguities regarding the application of ultrasound in detection of intestinal obstruction. This study aimed to evaluate the diagnostic accuracy of ultrasound in diagnosis of intestinal obstruction. Methods: This cross-sectional study was performed on patients with symptoms and signs of bowel obstruction between November19 and July 2020 in Shohadaye-Tajrish and Imam Hossein General Hospitals, Tehran, Iran. After a brief explanation and getting verbal consent, the patients underwent ultrasound examination in the emergency department by the emergency medicine resident. The results of ultrasound were compared with the surgical findings as the gold standard. Results: 24 patients with the mean age of 57.50±18.26 (range: 28 – 81) years were studied (58.3% male). Ultrasonography findings revealed the lumen diameter ≥ 2.5 cm in 21 (87.5%) cases, wall thickness ≥ 3 mm in 3 (12.5%) cases and inter-loop free fluid in 3 (12.5%) cases. Sensitivity, positive predictive value, and accuracy of ultrasound in detection of intestinal obstruction were found to be 85.00% (95%CI: 61.13 – 96.03), 80.95% (95%CI: 57.42 – 93.71), and 70.83% (95%CI: 48.91 – 87.38), respectively. Conclusion: It seems that point-of-care ultrasound has good sensitivity and accuracy in detection of intestinal obstruction when performed in the emergency department by a trained emergency medicine resident.